2018
DOI: 10.15417/issn.1852-7434.2018.83.2.760
|View full text |Cite
|
Sign up to set email alerts
|

Trasplante osteocondral autólogo para tratar lesiones osteocondrales de la rodilla: evaluación de 62 pacientes con un seguimiento promedio de ocho años. [Osteochondral autograft transplantation for the treatment of osteochondral injuries of the knee: evaluation of 62 patients with an average follow-up of 8 years.]

Abstract: <p><strong>Introducción</strong></p><p>El trasplante osteocondral autólogo es una alternativa quirúrgica en lesiones focales del cartílago articular. El objetivo de nuestro trabajo fue evaluar una serie de 62 pacientes tratados con mosaicoplastía de rodilla con 8 años promedio de seguimiento.</p><p><strong>Material y métodos</strong></p><p>Evaluamos retrospectivamente 62 pacientes operados con mosaicoplastía entre el año 2001 y 2014. Se incluyer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Regarding only patellofemoral articular defects, 10 better outcomes have been demonstrated in an athletic population similar to the population studied by Gudas et al Furthermore, another recent series, which included 12 patellofemoral lesions within a sample of 62 patients, found that OAT is a good alternative for the treatment of focal cartilage defects, with good results in long-term follow-up (mean follow-up of 8 years). 33 Following the trend of recent evidence, this review has shown that OAT or mosaicplasty is a useful alternative for the treatment of focal cartilage defects in the patella, with most patients reporting excellent functional outcomes at 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding only patellofemoral articular defects, 10 better outcomes have been demonstrated in an athletic population similar to the population studied by Gudas et al Furthermore, another recent series, which included 12 patellofemoral lesions within a sample of 62 patients, found that OAT is a good alternative for the treatment of focal cartilage defects, with good results in long-term follow-up (mean follow-up of 8 years). 33 Following the trend of recent evidence, this review has shown that OAT or mosaicplasty is a useful alternative for the treatment of focal cartilage defects in the patella, with most patients reporting excellent functional outcomes at 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 98%